Partial characterization of a tymovirus infecting passion fruit in Colombia, South America - Morales, Francisco José; Lozano Potes, Iván; Castaño, M.; Arroyave, José A.; Velasco, Ana Cecilia; Varón de Agudelo, Francia (2002)
A tymovirus was isolated from passion fruit plants with conspicuous yellow mosaic leaf symptoms in Colombia. Partial sequencing of its genome showed that this virus is distinct from other tymoviruses for which nucleotide sequences are available; it had only 60 76% homology with the closest related tymovirus species, Kennedya yellow mosaic virus. However, the pathogenic and antigenic properties of the Colombian tymovirus are similar to those of Passion fruit yellow mosaic virus (PFYMV), a tymovirus that infects Passiflora spp that has previously been found in Brazil. Therefore, this name will be retained for the tymovirus occurring in Colombia until a Brazilian isolate of PFYMV is characterized at the molecular level.